The scope of a comprehensive primary healthcare approach in addressing the rising burden of noncommunicable diseases - Senthilkumar Ramasamy; Suganya Panneerselvam; Pitchaimani Govindharaj; Sanjana Agarwal (International Journal of Noncommunicable Diseases)
Noncommunicable diseases (NCDs) have emerged as a leading global health challenge and globally account for three-fifths of morbidity and mortality. Hypertension and diabetes are the two leading causes of NCDs in terms of magnitude; one in four people in India has high blood pressure, and one in ten has excessive blood sugar. India is struggling to tackle the rising burden of NCDs due to the rapid progression. This review aims to understand the existing role of the primary healthcare (PHC) model in addressing the NCD’s burden in India. This study employed a narrative desk review design, which involves systematically collecting and synthesizing existing research and data from various sources to provide a comprehensive overview of the topic. An estimate shows that 80% of the NCDs and premature deaths related to NCDs can be preventable and manageable if detected in an earlier stage. To expand the service closer to the community, major importance was given to population-based screening through the frontline healthcare workers who provide service in the PHC system. To achieve the Sustainable Development Goal by 2030, it is crucial to strengthen the PHC system and empower mid-level health providers, including community health officers, rural health organizers, auxiliary nurses, and midwives.